1996
DOI: 10.1038/ki.1996.96
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids and acidosis stimulate protein and amino acid catabolism in vivo

Abstract: We have shown that chronic metabolic acidosis in awake rats accelerates whole body protein turnover using stochastic modeling and a continuous infusion of L-[1-13C] leucine. To delineate the role that glucocorticoids play in mediating these catabolic responses, we measured protein turnover in awake, chronically catheterized, adrenalectomized rats in the presence or absence of glucocorticoids and/or a NH4Cl feeding regimen which induced chronic metabolic acidosis. In adrenalectomized rats receiving no glucocort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 20 publications
3
58
0
Order By: Relevance
“…Adrenalectomy inhibited this effect of acidosis, but provision of low or high doses of dexamethasone to adrenalectomized rats once again allowed acidosis to stimulate protein degradation (4). Similar results were found for acidosis-stimulated muscle leucine oxidation (18), and for acidosis-induced increases in the abundance of mRNAs encoding polyubiquitin and the C2 and C9 subunits of the 26S proteosome (19), all of which contribute to acidosis-induced protein breakdown. Similarly, in cultured BC 3 H1 cells maintained in 1% serum, increased protein degradation was not seen with media acidification or dexamethasone alone, but was seen with media acidification and dexamethasone together (20).…”
Section: Discussionsupporting
confidence: 70%
“…Adrenalectomy inhibited this effect of acidosis, but provision of low or high doses of dexamethasone to adrenalectomized rats once again allowed acidosis to stimulate protein degradation (4). Similar results were found for acidosis-stimulated muscle leucine oxidation (18), and for acidosis-induced increases in the abundance of mRNAs encoding polyubiquitin and the C2 and C9 subunits of the 26S proteosome (19), all of which contribute to acidosis-induced protein breakdown. Similarly, in cultured BC 3 H1 cells maintained in 1% serum, increased protein degradation was not seen with media acidification or dexamethasone alone, but was seen with media acidification and dexamethasone together (20).…”
Section: Discussionsupporting
confidence: 70%
“…In our cohort, the likelihood of significant hyperkalemia increased with decrease in serum bicarbonate. Acidosis also induces protein energy wasting through increased protein catabolism, decreased protein synthesis, and increased insulin resistance (1)(2)(3)(4). Other potential mechanisms include systemic inflammation and a more rapid loss of residual renal function (11)(12)(13)(31)(32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with CKD, uncorrected metabolic acidosis leads to clinically significant consequences like protein energy wasting and bone disease, and in hemodialysis (HD) patients, it is associated with higher death risk (1)(2)(3)(4)(5)(6)(7). Clinical trials have shown that correction of metabolic acidosis results in improvements in protein energy wasting and reduction of hospitalizations of peritoneal dialysis (PD) patients (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Feeding CRF rats a high-protein diet did not raise the plasma concentrations of these essential amino acids, suggesting that overriding conditions (i.e., acidosis or a hormonal imbalance) accelerated their degradation (25). We and others have identified glucocorticoids as a physiological signal that increases branched-chain ketoacid dehydrogenase (BCKD) activity in muscle of adrenalectomized rats (1,14,21,28) and in LLC-PK 1 renal epithelial cells that had been stably transfected to express glucocorticoid receptors [LLC-PK1-GR101 cells (35)]. The BCKD enzyme complex is responsible for the irreversible degradation of BCAAs.…”
mentioning
confidence: 99%